Modulation of Antibiotic Activity Against Streptococcus pneumoniae by N-acetylcysteine and ascorbic acid - Dini Agustina; Bagus Dwi Kurniawan; Intan Palupi (Journal of Agromedicine and Medical Sciences, 2016)
Streptococcus pneumoniae is one of the bacterial pathogens that cause pneumonia. Pneumonia is the biggest cause of infant mortality in Indonesia around 23%. The main therapy pneumonia is antibiotics, but in some cases combined with ascorbic acid or N-acetylcysteine, which serves as a complementary therapy. The purpose of this study was to determine the effect of adding ascorbic acid or N-acetylcysteine ​​on antibiotics towards the growth of S. pneumoniae in vitro. The method used in this research is the method of germ-disc diffusion susceptibility test with S. pneumoniae growth inhibition is indicated by the formation of inhibition zone. Positive controls used clindamycin and erythromycin. The average diameter of inhibition zone on the negative control, positive control, and treatment of 1 to 5 on the addition of clindamycin with ascorbic acid are respectively 5; 24.12; 24.62; 26.08; 27.58; 28.74; and 29.76 mm. The data has a strong correlation to the Pearson test (R=+0,910). On a logarithmic regression analysis found minimal concentration of ascorbic acid can inhibit is 1.767 mg/ml. While the addition of erythromycin with N-acetylcysteine ​​are respectively 28.02; 25.62; 23.46; 22.42; and 21.68 mm. Pearson correlation test results of these data are the opposite relationship between the diameter of inhibition zone and the concentration of N-acetylcysteine ​​with a very strong correlation coefficient. Logarithmic regression of the minimum concentration of N-acetylcysteine ​​which may decrease the antibacterial activity of erythromycin inhibit the growth of Sreptococcus pneumoniae amounted 1,66mg/ml. It is concluded that ascorbic acid increases the activity of clindamycin in inhibiting the growth of S. pneumoniae in vitro and N-acetylcysteine ​​may decrease the antibacterial activity of erythromycin in inhibiting the growth of S. pneumoniae in vitro. Keywords: S. Pneumoniae, ascorbic acid, N-asetilsitein, inhibition zone